Evidence for independent instances of chromosome number reduction in the genus Pseudopaludicola (Anura: Leptodactylidae) - Cardozo, Darío; Boeris, Juan Martín; Ferro, Juan Martín; Borteiro, Claudio; Kolenc, Francisco; Suárez, Pablo; Netto, Flavia; Brusquetti, Francisco [UNESP]; Baldo, Diego (My University, 2016)
We describe the chromosome morphology, C-bands, NORs position, and DAPI/CMA3 staining of five species of Pseudopaludicola (P. boliviana, P. canga, P. falcipes, P. mystacalis, and P. ternetzi) from several populations from Argentina, Brazil, Paraguay, and Uruguay. In addition, the telomeric sequence locations of P. mystacalis and P. canga are evaluated using FISH. We re-analyse the progressive reduction of chromosome numbers recently proposed for the genus by optimisation of character basic chromosome numbers (x) and fundamental chromosome numbers (FN) on current phylogenetic hypotheses. Our evidence supports a progressive reduction of chromosome numbers in Pseudopaludicola, and multiple origins of the karyotype 2n = 20. Additionally, we discuss the interpretation of the current Pseudopaludicola phylogenetic hypothesis and a series of inconsistencies in the chromosome literature for the genus.
Keywords: C-bands; Character optimisation; Chromosome reduction; CMA3; DAPI; NORs